SOCIOECONOMIC STATUS AND REPRODUCTIVE HEALTH OF MOTHERS FROM DIFFERENT ETHNIC GROUPS IN NORTH MACEDONIA - Livrinova, Vesna (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, Co-publisher Scientific foundation Spiroski, 2024)
A reproductive health framework would provide a broader programmatic focus that could bring needed attention to such issues as sexually transmitted diseases, infertility, abortion and women‘s empowerment generally. In order to analyze the elements of the reproductive health of our population, a one-year study was conducted that included 400 women in labor. Material and methods: Age, parity, number of pregnancies and deliveries antepartal controls, supplements intake, place of residence, etc. were analyzed. A descriptive analysis and statistical significance were made providing women‘s ethnicity. The results showed that the highest average age of women giving birth was registered among Macedonian women and it was 31.5 ± 5.4 years, and the lowest among Roma women 22.9 ± 5.4 years. The highest average number of deliveries among women in labor was observed in Roma and Bosnian women and it was 2.4±1.2 deliveries, and the lowest rate in Serbian women 1.3±0.6. The difference was statistically significant. It can be concluded that the emancipation of women, the level of education and the employment of women among all ethnic groups are the most important factors in the urban region. The traditions of religion and ethnicity are fundamental in family planning and have the main influence on women‘s reproductive life.
Keywords: social; reproductive health; ethnicity